PRESERVASI FUNGSI NEUROKOGNITIF PADA PASIEN METASTASIS OTAK YANG MENJALANI RADIOTERAPI - Ayu Santika Santaningrum; Henry Kodrat (PERDOSNI, 2021)
Brain metastasis is a major factor of mortality and morbidity in cancer patients, leading to poor prognosis in patient survival. Whole-brain radiotherapy (WBRT) has remained preferred therapy to prolong survival in patients with brain metastases. Neurocognitive decline due to WBRT affects the quality of life of patients, thus encouraging development of techniques and strategies in radiation therapy for brain metastatic patients. Stereotactic radiosurgery (SRS) shows its ability to preserve cognitive function and improve quality of life in patients with limited number of intracranial metastatic lesions, with better survival at age ≤50 years. For patients who undergo WBRT, hippocampal avoidance (HA)-WBRT technique, addition of memantine, or combination of both showed significantly better neurocognitive preservation, without affecting toxicity and survival in patients with brain metastases. Keywords: brain metastases, hippocampal avoidance, memantine, stereotactic radiosurgery, whole-brain radiotherapy